Boundedly solvable extensions of delay differential operators - (:unkn) unknown (Texas State University - San Marcos, 2017)
We describe all boundedly solvable extensions of minimal operators generated by first-order linear delay differential operators in Hilbert spaces of vector-functions on finite intervals. Also, we study the structure of spectrum of these extensions. To do this we use methods from operator theory. © 2017 Texas State University.
Keywords: Boundedly solvable operator; Delay differential expression